2010
DOI: 10.1586/egh.10.29
|View full text |Cite
|
Sign up to set email alerts
|

Liver fibrosis in biliary atresia

Abstract: Biliary atresia (BA) is the most common cholestatic liver disorder requiring liver transplantation in children. Hepatic fibrosis is not only a universal and prominent feature of BA, it is also the most important predictor of outcome following portoenterostomy (PE). Without PE, the progression of hepatic fibrosis is quite dramatic, such that liver cirrhosis is established within a few weeks after birth. Etiologies and molecular networks underpinning such an expeditious fibrogenic process have not been well esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 92 publications
2
31
0
Order By: Relevance
“…Hepatic fibrosis is a universal feature of biliary atresia and its progression to severe fibrosis and cirrhosis early in life is unique to this disorder [6]. Although biopsy has traditionally been required to assess liver fibrosis, several recent studies in children and adults have demonstrated that US shear wave elastography (SWE) can be used to detect and quantify liver fibrosis [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic fibrosis is a universal feature of biliary atresia and its progression to severe fibrosis and cirrhosis early in life is unique to this disorder [6]. Although biopsy has traditionally been required to assess liver fibrosis, several recent studies in children and adults have demonstrated that US shear wave elastography (SWE) can be used to detect and quantify liver fibrosis [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…An enigmatic characteristic of this entity is the rapid progression of fibrosis, leading to cirrhosis in the first weeks of life. A combination of genetic and environmental factors has been proposed to explain it, giving rise to a particularly intense fibrogenesis driven by an ongoing immune activation that may persist even after surgical restoration of bile flow [5,6]. After the Kasai portoenterostomy >50% of patients will clear jaundice if surgery is performed before 60 days of age but, unfortunately, almost all will already show an advanced stage of fibrosis or cirrhosis by that time (Figure 28.2) [7].…”
Section: Biliary Atresiamentioning
confidence: 99%
“…However, both studies relate to biliary atresia, in which occlusion of the bile duct leads to cholestasis with secondary fibrosis of the liver [38] It is therefore conceivable, that the high miR-222 levels found in these studies do not directly correlate with pro-fibrotic signaling, but rather relate to increased stellate cell proliferation with secondary effects on the degree of cholestasis and fibrosis.…”
Section: Conclusion and Discussionmentioning
confidence: 86%
“…Subsequently, the eIF4F complex recruits the 40S ribosomal subunit and joins with the 60S ribosomal subunit at the AUG codon to begin elongation. RISC is postulated to repress initiation of translation by competing with eIF4E to bind to the 5' terminal cap [36,37], and by blocking the association of the 60S ribosomal subunit with the 40S pre-initiation complex [38].…”
Section: Mirna-induced Posttranscriptional Repressionmentioning
confidence: 99%
See 1 more Smart Citation